Konminualʹnostʺ/diskretnostʺ — stilevaâ čerta diskursa - Baranov, Anatolij G. (Stylistyka, 2020)
The predominant way of stylistic investigation - up till nowadays - follows the di chotomie ‘token-type’ principle. It is argued here that the comprehensive study of style be carried along the rhetoric-interpretative lineš, which requires a letrachotomic ap- proach (thinking - discourse - genre - utterance), thinking and utterance levels being of paramount importance. So, one should distinguish style of thinking, utterance style, genre style and discourse style. The analysis of continuity/discreteness is carried oul on four varieties of discourse: business, scientific, everyday (set in f literary one ) and poetic. The results show that the antinomy o f continuity/discreteness is highly varřable in each ilem of the antinomy - from continuity to discreteness and backwards; the scale o f variability dependent, though, on the type o f discourse. This fact shows that this antinomy might be treated as a stylistic feature of communication, alongside with other features of textuality.